SMARTPHONE APPLICATION VOICE OVER INFORMATION SYSTEM FOR VISUALLY IMPAIRED IN WEST JAVA “SI VOTUN JABAR” - Indah Dwianti Mardinata (Jurnal Sosioteknologi, 2022)
Through Law Number 14 of 2008 concerning Information Disclosure, the government has begun to open a portal for information disclosure for the public, including persons with disabilities who are blind. Therefore, we need an android application based on voice over for the blind in West Java for the needs of digital public information requests and evaluate the application based on the ease of service access, the accuracy of the data, and information requested. This research uses qualitative methods and the type of research is action research. The interview technique was the method chosen to collect data and then used Miles and Huberman analysis techniques in the form of data reduction and presentation and drawing conclusions. From this study, it was found that the West Java Si Votun application for the blind was good. Judging from the ease of access, the operation is easy, the accuracy of the data provided is precise, and the narrative details are easy to understand.